An electrodeposited Ni-P-WS2 coating with combined super-hydrophobicity and self-lubricating properties. (10th August 2017) - He, Y.; Sun, W.T.; Wang, S.C.; Reed, P.A.S.; Walsh, F.C.
Abstract: Self-lubrication and super-hydrophobicity are sought-after qualities in industrial surface finishing but such properties are rarely combined in a single coating. The present studies have produced a low-friction, superhydrophic Ni-P-WS2 coating by a versatile one-pot, single-step electrodeposition. By adjusting the particle and surfactant concentrations, a hierarchical surface, consisting of micron-sized protrusion arrays and submicron-sized bumps on the top and exhibiting a high water contact angle of 157 deg was achieved. Furthermore, mechanical and friction properties are characterized, revealing that sufficient WS2 embedded in the Ni-P coatings enables a reduced friction coefficient of 0.17 by the formation of a self-lubricating tribofilm.